PANCASILA: A Contemporary Application of Maqasid al-Shari‘ah? (State Islamic University (UIN) of Sunan Ampel Surabaya, 2015)
This paper proposes that the traditional principle of maqasid al-Shari‘ah, or the higher intentions and objecttives of Islamic law, can go beyond the realm of theoretical Islamic jurisprudence and is made manifest in practical politics. I argue that the most robust example of this phenomenon occurs in Indonesia. I therefore examine whether or not the concept of Indonesia’s ‘secular’ and nationalistic doctrine of Pancasila, the Five Principles, can be construed as a contemporary application of maqasid al-Shari‘ah. This study strives to link the classical jurisprudential tool of maqasid al-Shari‘ah, as discussed by al-Ghazālī (d. 1111), al-Shātibī (d. 1388) and more recently by Muhammad al-Tahir Ibn ‘Āshūr (d. 1973), with the contemporary model of Pancasila.